An Assessment Of The Impact Of The Planting For Food And Jobs Policy On Smallholder Farmers Food Security In The Wa West District - Nurideen, F. (University of Ghana, 2019)
An important goal of government agricultural sector policies is to improve food security through high agricultural production and job creation. Implementation of the flagship policy of the government of Ghana dubbed the ―Planting for Food and Jobs‖ started in 2017. After three years of implementation, the study sought to examine whether the policy has impacted on food security among smallholder farmers in the Wa West District of the Upper West Region. The study also examined the kind of on-farm jobs created, youth involvement as well as the experiences of farmers with the programme. The study employed a quasi-experimental cross-sectional survey design involving semi structured questionnaire administered to 200 farmers of whom 62 represented the participant group and 138 the non-participant group. Logit regression was employed to identify the factors that determine household participation in the programme. Age, education, capital access, monthly income, infrastructure, community group association and assets were found to have statistically significance in association with the probability to participate in the Planting for Food and Jobs Programme. A propensity score matching technique was applied to assess the impact of the programme on food security. At the end of the survey, participation in the PFJ has a significantly higher average food security than the non-participants
MA. Research And Public Policy
Keywords: Smallholder Farmers; Food Security